e-RetailTest: Scale to Assess the Attitude of Consumers towards E-Commerce in the Retail Sector - García-Salirrosas, Elizabeth Emperatriz (2023)
Changes in consumer behavior are driven by tastes and preferences that change over time as their socioeconomic conditions change. The objective of this study was to validate the psychometric characteristics of the e-RetailTest scale, created to measure consumer attitudes towards online shopping in developing countries, particularly in the Peruvian market. The e-RetailTest evaluates five variables present in the online purchase process: (a) quality of web design, (b) risk when making a purchase, (c) customer service, (d) security and (e) satisfaction, with a total of twenty items using a Likert scale. A total of 422 valid responses were collected from Peruvian consumers who had had online shopping experience in the retail sector. Statistically, we worked with the AFE exploratory factor analysis and the AFC confirmatory factor analysis. The results suggest that this first version of the e-RetailTest presents adequate psychometric evidence to measure the attitude of consumers towards online purchases in the retail sector in the Peruvian market. Thus, it seeks to contribute to the advancement of the study of these important variables of Latin American consumer behavior.